PENGARUH INFLASI DAN SUKU BUNGA PADA BANK KONVENSIONAL TERHADAP PEMBIAYAAN MURABAHAH (STUDI KASUS BANK SYARIAH INDONESIA) - B01111013, KRISNADI (Jurnal Pembangunan dan Pemerataan, 2016)
Islamic Banking has shown important roles in the principle of mutual assistance, which is reflected in the personality of the people of Indonesia. So it can compete in the banking sector in recent decades. This research aims to test the effect of inflation and interest rates on conventional banks to the demand of murabahah financing (Study case on Islamic banks in Indonesia). The independent variables in this research conclude the rate of inflation (X1) and interest rates of convetional banks (X2). The dependent variable is murabahah financing (Y). The data get from website of Bank Indonesia/OJK. It is range is 4 years from 2011 to 2015. Data analysis is multiple regression. The results of this research show that Inflation has positive and significant impact on the demand of murabahah financing on Islamic Banks in Indonesia, and also the interest rates of conventional banks have positive and significant impact on the demand of murabahah financing on Islamic Banks in Indonesia. There is the influence of Inflation and Interest Rates of conventional banks simultaneously on demand of murabahah financing on Islamic banks in Indonesia. It is indicated by a great coefficient of determination. Keywords: Inflation, Interest rate of Conventional Banks, Demand of murabahah financing